2012
DOI: 10.4136/ambi-agua.925
|View full text |Cite
|
Sign up to set email alerts
|

Remoção de nitrogênio e fósforo do esgoto sanitário em um sistema de alagados construídos utilizando o capim vetiver

Abstract: RESUMONo presente trabalho objetivou-se avaliar a eficiência do capim vetiver (Vetiveria zizanioides L. Nash) na remoção de nitrogênio e fósforo do esgoto sanitário, em um sistema de tratamento do tipo alagados construídos. A unidade experimental possuiu doze módulos de tratamento, cada um preenchido com camadas sobrepostas de substrato. Do fundo até a superfície foram utilizados: 0,15 m de brita # 3; 0,10 m de brita # 1; 0,20 m de areia lavada e 0,05 m de brita # 1. No interior dos módulos, o esgoto foi manti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 4 publications
1
9
0
3
Order By: Relevance
“…In the samplings with the best results, it was observed that the treatment using horizontal subsurface-flow CWS was able to remove 76.5, 50.5, 37.4 and 64.4% of TKN, ammonia, nitrate and nitrite, respectively. These results are similar to those observed by many authors (Ucker et al, 2012;Matos et al, 2010;Tanner et al, 2005). It is important to point out that no chemical treatment was performed in the present study, only biological treatment for the removal of pollutants.…”
Section: Guimares Et Al 4547supporting
confidence: 81%
See 4 more Smart Citations
“…In the samplings with the best results, it was observed that the treatment using horizontal subsurface-flow CWS was able to remove 76.5, 50.5, 37.4 and 64.4% of TKN, ammonia, nitrate and nitrite, respectively. These results are similar to those observed by many authors (Ucker et al, 2012;Matos et al, 2010;Tanner et al, 2005). It is important to point out that no chemical treatment was performed in the present study, only biological treatment for the removal of pollutants.…”
Section: Guimares Et Al 4547supporting
confidence: 81%
“…Matos et al (2010), using constructed wetland systems in the treatment of swine farming wastewater (PFW), obtained total N removal efficiency of 64% in systems cultivated with Tifton 85, and 61% for systems cultivated with Alternanthera. Ucker et al (2012) obtained good efficiency in the removal of ammonia in CWSs cultivated with vetiver.…”
Section: Guimares Et Al 4547mentioning
confidence: 95%
See 3 more Smart Citations